3D knitted energy storage textiles using MXene-coated yarns. (April 2020) - Levitt, Ariana; Hegh, Dylan; Phillips, Patrick; Uzun, Simge; Anayee, Mark; Razal, Joselito M.; Gogotsi, Yury; Dion, Genevieve
Graphical abstract: Abstract: Textile-based energy storage devices offer an exciting replacement for bulky and uncomfortable batteries in commercial smart garments. Fiber and yarn-based supercapacitors, currently dominating research in this field, have demonstrated excellent performance below ∼4 cm in length, but suffer at longer lengths due to increased resistance. Herein, a new architecture of wearable energy storage devices, 3D knitted supercapacitors, is designed and prototyped with the intention of exploiting the architecture of a knit textile to improve the performance of long yarn electrodes. While Computer-Aided Design (CAD) knitting is a ubiquitous technology for producing textiles, knitted energy storage devices have been largely unexplored due to the need for meters of highly conductive yarn electrodes that meet the strenuous strength and flexibility requirements for CAD knitting. MXenes, a family of solution processable and conductive two-dimensional (2D) materials, have been realized as inks, slurries, pastes, and now dyes for the development of on-paper, on-plastic, and on-textile microsupercapacitor electrodes. In this work, Ti3 C2 T x MXene was adopted as an active material for coating meters of commercial natural and synthetic yarns, enabling the production of knitted planar microsupercapacitors. The impact on electrochemical performance of knit structure and geometry was systematically studied in an attempt to produce energy storing textiles with power and energy densities that can be used for practical applications. The resulting energy storing textiles demonstrate high capacitance, up to 707 mF cm −2 and 519 mF cm −2 at 2 mV s −1 in 1 M H3 PO4 and PVA-H3 PO4 gel electrolyte, respectively, and excellent cycling stability over 10, 000 cycles. This work represents an important step towards the mass production of MXene-based conductive yarns and 3D knitted energy storage devices and demonstrates how knit structure plays a significant role on device performance.